A Geometrical Account to Explain the Fat-Face Illusion. (December 2020) - Rawal, Amit; Tseng, Philip
Investigations of the "fat-face" illusion have unanimously agreed that the illusion is face-specific. Here, we offer several manipulations to highlight that the fat-face illusion is not restricted to the bottom image, isn't a property of internal features, facial contour/texture, and in general isn't even specific to faces. We propose the axis of horizontal asymmetry account to contextualize fat-face illusion as a geometry-led illusion.